Smart growth and its discontents : an examination of american and european approaches to local and regional sustainable development - Krueger, Rob (Documents d'Anàlisi Geogràfica, 2011)
Increasingly concepts of sustainable development are finding their way into local and regional development strategies. This is also true in the USA, though not through the Local Agenda 21 process, as is the case in much of the rest of the world. The approach to ‘sustainable development’ in the USA is a set of policy approaches collectively referred to as ‘smart growth’. Smart growth is sometimes referred to as a uniquely ‘American’ variant of sustainable development. In contrast to Local Agenda 21, smart growth has captured the imagination of American policy makers, at all spatial scales. Smart growth is most attractive as a local and regional development strategy. In this paper I explore compare Local Agenda 21 and Smart Growth in the context of the USA and Europe using secondary data sources and analysis as well as a case study from Massachusetts, USA.